Deep Sequencing of T-Cell Receptors for Monitoring Peripheral CD8+ T Cells in Chinese Advanced Non–Small-Cell Lung Cancer Patients Treated With the Anti–PD-L1 Antibody - Sheng, Jin; Wang, Huadi; Liu, Xiao; Deng, Yunyun; Yu, Yingying; Xu, Pengfei; Shou, Jiawei; Pan, Hong; Li, Hongsen; Zhou, Xiaoyun; Han, Weidong; Sun, Tao; et al. (Frontiers in Molecular Biosciences, 2021)
Background: Atezolizumab, a high-affinity engineered human anti-PD-L1 antibody, has produced a clinical benefit for patients with advanced non-small-cell lung cancer (NSCLC). However, associated with T cell regulation, the immuno-modulatory effect of PD-L1 blockade and its biomarker in peripheral immunity remains illustrated. Methods: In a prospective cohort with 12 Chinese advanced NSCLC patients who received atezolizumab 1200 mg every three weeks as a second-line treatment, blood samples were obtained before and six weeks after atezolizumab initiation, and when disease progression confirmed. Patients were classified into a response or progression group according to Response Evaluation Criteria in Solid Tumors (RECIST)1.1. Fresh peripheral blood mononuclear cells (PBMCs) from patients were stained with anti-human CD3, CD8, and PD-1 antibodies for flow cytometry analysis. T cell receptor (TCR) β chains of CD8+ T cells were analyzed by Next-Generation Sequencing (NGS) at the deep level. Diversity, clonality, and similarity of TCR have been calculated before and after treatment in both groups. Results: Clonal expansion with high PD1 expression was detected in all patients’ peripheral CD8+ T cells before the treatment of atezolizumab. Unlike the progression group, the diversity of TCR repertoire and singletons in the TCRβ pool, increased over time with atezolizumab administration, and the TCR repertoire dynamically changes in the response group. The percentage of CD8+ PD1high terminal exhausted T cells declined in the response group after the PD-L1 blockade. Two patterns of TCR changes among patients who receive PD-L1 targeted immunotherapy were observed. Conclusions: Deep sequencing of the T-cell receptors confirmed the existence of CD8+ PD1high T cells with an exhaustion phenotype in Chinese NSCLC patients. Our study demonstrated that efficient anti-PD-L1 therapy could reshape the TCR repertoire for anti-tumor. Furthermore, singleton frequency may help us select patients who are sensitive to anti-PD-L1 immunotherapy.